Selected Bibliography of Completed Theses and Dissertations Related to North Carolina Subjects. - MILLER, ANNE (North Carolina Historical Review, 2026)
The article focuses on a comprehensive bibliography of theses and dissertations related to North Carolina subjects, compiled by Anne Miller. Topics include the scope of the bibliography covering works from 1974 to 1978, the sources from which these academic works were collected, and the organization of entries by author, subject, and degree to facilitate research on North Carolina history and topics.